2005
DOI: 10.1055/s-2005-873128
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide Isolated fromAndrographis paniculataInduces Cell Cycle Arrest and Mitochondrial-Mediated Apoptosis in Human Leukemic HL-60 Cells

Abstract: The in vitro cytotoxicities of the ethanol extract of Andrographis paniculata (APE) and its main diterpenoid components were evaluated in various cancer cells. APE was found to be significantly growth inhibitory to human acute myeloid leukemic HL-60 cells with an IC (50) value of 14.01 microg/mL after 24 h of treatment. Among the three main diterpenoids in A. paniculata, andrographolide exhibited the highest degree of cytotoxicity followed by deoxyandrographolide while neoandrographolide was the least effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 10 publications
6
106
1
Order By: Relevance
“…Therefore, it is urgent to search for natural drug to further improve the outcome of melanoma patients. Andro, one of the major components of Andrographis paniculata, has been used as an effective, safe and antitumor drug for several centuries (25). In the present study, we revealed that Andro could inhibit proliferation of human melanoma cell lines through inducing G2/M cycle arrest and cell apoptosis.…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, it is urgent to search for natural drug to further improve the outcome of melanoma patients. Andro, one of the major components of Andrographis paniculata, has been used as an effective, safe and antitumor drug for several centuries (25). In the present study, we revealed that Andro could inhibit proliferation of human melanoma cell lines through inducing G2/M cycle arrest and cell apoptosis.…”
Section: Discussionmentioning
confidence: 52%
“…They suggested that the anti-tumor effect of andrographolide could partly be attributed to its apoptotic and anti-inflammatory potential during DMBA induced hamster buccal pouch carcinogenesis. Also, previous studies demonstrated the apoptotic and anti-inflammatory potential of andrographolide in various cancer cells (Cheung et al, 2005;Lee et al, 2011;. It has been demonstrated that andrographolide suppressed VEGF expression in prostate cancer and pulmonary tumors (Zhao et al, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…33) Likewise, Andrographis paniculata extract and andrographolide was found to significantly inhibit growth of human acute myeloid leukemic cells by inducing cell cycle arrest and affecting an intrinsic mitochondria-dependent pathway of apoptosis by regulating expression of some pro-apoptotic markers, namely causing chromosomal DNA fragmentations, an occurrence of apoptosis, induction of Bcl-2-associated X protein (Bax) expression, and decrease of B-cell lymphoma 2 (Bcl-2) proteins in the inhibited cells. 34) Moreover, induction of cell cycle arrest at G2/M phase and a late apoptosis of the cells with the collapse of mitochondrial membrane potential and an intracellular increase of hydrogen peroxide but a decrease of superoxide radicals and reduction of glutathione have been reported as well. 35) The cytotoxic effect of andrographolide on HepG2 cells was suggested to be the primary attribute to the induction of cell cycle arrest via the alteration of cellular redox status.…”
Section: Immunological Potentialmentioning
confidence: 99%
“…5) In Thailand, this plant was selected by the Ministry of Public Health as one of the medicinal plants to be included in "The National List of Essential Drugs A.D. 1999" (List of Herbal Medicinal Products). 6) Extensive research has revealed that Andrographis paniculata has a surprisingly broad range of pharmacological effects and some of them are extremely beneficial, such as antiinflammatory, [7][8][9][10][11] antidiarrhoeal, 12,13) antiviral, 14) anti-malarial, 15,16) hepatoprotective, [17][18][19][20][21][22][23][24][25][26][27][28][29] cardiovascular, 30,31) anticancer, [32][33][34][35][36][37][38][39] and immunostimulatory [40][41][42][43][44] activities. On the other hand, male reproductive toxicity 45) and cytotoxicity 46) of this plant have been reported as well.…”
Section: Introductionmentioning
confidence: 99%